EVALUASI TANAMAN REVEGETASI PADA PROGRAM RESTORASI GAMBUT DI KAWASAN HUTAN LINDUNG LIANG ANGGANG KALIMANTAN SELATAN - Aris Nurohman; Hamdani Fauzi; Sulaiman Bakri (Jurnal Sylva Scienteae, 2020)
Indonesia has 136.17 million hectares (ha) of forest, of which 20 million ha is peat forest. Meanwhile, Kalimantan with an area of 746,305 km2 of which 539,460 km2 (70%) is in Indonesian territory. The purpose of this study was to evaluate peatland revegetation plants and analyze the health of the types of plants planted on peat revegetation in the peat restoration program.Some growth parameters are measured such as the percentage of life, plant height, plant diameter, and plant health. The results of this study are 1,763 individuals, consisting of 12 types of plants. The highest number of plants is the Prince with 372 individuals. The fewest plants are eucalyptus and sapodilla.Keywords: Revegetation; Diameter; Height; Plant Health